Superior and Inferior Ophthalmic Vein Thrombosis in the Setting of Lung Cancer - Nawal Habib; Kimberly Lessard (Case Reports in Oncological Medicine)
Superior ophthalmic vein thrombosis is extremely rare and is often associated with orbital inflammation/infection, systemic/local tumors, hypercoagulable states, autoimmune conditions, and rarely carotid cavernous fistula. Clinical features include abrupt onset of painful proptosis, chemosis, ophthalmoplegia, and diminished visual acuity. Prompt diagnosis and treatment are essential to prevent permanent blindness. Management options for this medical emergency include antibiotics, steroids, and/or anticoagulation. We present a case of superior ophthalmic vein thrombosis with left cavernous sinus thrombosis in the setting of newly diagnosed malignancy.